Penguatan Profil Pelajar Pancasila Menggunakan Model Value Clarification Technique (VCT) Tipe Percontohan Pada Pendidikan Pancasila Sekolah Dasar - Soma Triharyoso; Maha Lastasa Buju Basafpipana Habaridota; Syarifah Asmiati (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
This study describes the strengthening of the Pancasila Student Profile using the Value Clarification Technique (VCT) model in the Civics Education learning of the topic "Obeying Rules in My Surroundings" in Class II A of State Elementary School 03 Pontianak Timur for the 2024/2025 academic year. The method used is a descriptive qualitative approach, with a purposive sample of the class teacher and students. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, presentation, conclusion drawing, and verification. The results indicate that (1) the lesson planning includes the creation of teaching modules that emphasize the importance of obeying rules and the values contained within; (2) the implementation of the lessons conducted by the teacher strengthens the Pancasila student profile dimension of critical thinking through the Value Clarification Technique (VCT), helping students recognize behavioral values through Pancasila education; and (3) evaluation is carried out using Student Work Sheets (LKPD) which facilitate reflection and assessment of students' ability to identify behavioral values.